The Evolution and Trend of The Use of Digital Assessment Instruments in Project-Based Learning in Online Learning Environment - Eva Nauli Taib; Syarifah Farissi Hamama; Nurmahni Harahap (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study examined the evolution and trends in the use of digital assessment instruments in project-based learning (PBL) in an online learning environment. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines to ensure transparency and rigor. The review included 44 articles published between 2019 and 2024. The data collection process involved searching using various keywords and platforms such as Scopus and Google Scholar, facilitated by Publish or Perish (PoP), as well as article selection using Rayyan AI and Claude AI to ensure suitability to the study criteria. Data were analyzed using thematic synthesis to identify key patterns and trends in the application of these digital tools. Findings indicated the need for: (1) integration of various assessment modalities for effective online learning, (2) development of pedagogical frameworks that support new technologies, and (3) standardization of digital assessment systems. In addition, the review suggests further research to assess the long-term effectiveness and impact of new technology-based instruments on learning outcomes. The findings provide a comprehensive understanding of the evolution of digital assessment instruments in online learning and provide evidence-based recommendations for future development.